GRADIENTS IN PROKARIOTIC COMMUNITY AND GEOCHEMISTRY IN AN ALPINE ROCK GLACIER ASSOCIATED POND - MANIA, ILARIA; COLOMBO, NICOLA; FREPPAZ, Michele; MARTIN, Maria; GORRA, ROBERTA; Anesio A. (2017)
Rock glaciers (RGs) are geomorphological features widespread in high-elevation alpine environments, consisting of slow-flowing mixtures of rocks and ice, and are considered indicators of ice-rich permafrost presence. Due to their capability to influence waters passing through and originating from them, RGs have the potential to influence connected alpine water bodies, both in terms of water geochemistry and, as pointed out mainly in the last years, overall ecosystem ecology. In this study, we describe archaeal and bacterial communities in the sediments of an alpine RGassociated pond (Col d’Olen Rock Glacier, Valle d’Aosta, Italy), characterized by serpentinitic mineralogy. Abundance and diversity of 16S rRNA genes have been assessed by qPCR and MiSeq Illumina sequencing, along a distance gradient from the RG front. We have also analysed the microbial community composition in relationship with different geochemical factors (DOC, TDN, pH, nitrogen forms, major anions and cations), focusing on the sediment-water interface as a major location for biogeochemical cycling and weathering processes. While community composition shows a certain degree of variation across the gradient, as well as Na+, Ca2+ and Mg2+ concentration, increasing with distance from the RG front, microbial abundance and several geochemical parameters (pH, DOC, TDN, NH4 + and Si) follow an apparently depth-based distribution pattern. Our results suggest that a complex net of environmental factors, such as water depth, in addition to the environmental gradient derived from icemelt waters, can have a significant impact on the distribution of the prokariotic community and geochemistry along the Col d’Olen Rock Glacier Pond.